Reflective playwork for all who work with children - Kilvington, Jacky; Wood, Ali (Bloomsbury Academic, 2018)
This text provides an introduction to playwork values, principles and practice for all who work with children. It recognizes that play is a need for all, and seeks to encourage the provision of time and space for all children to freely enjoy its benefits.